Microbiota and the Response to Vaccines Against Respiratory Virus - Gonçalves, João I. B.; Borges, Thiago J.; de Souza, Ana Paula Duarte (Frontiers in Immunology, 2022)
This minireview describes the role of gut and lung microbiota during respiratory viral infection and discusses the implication of the microbiota composition on the immune responses generated by the vaccines designed to protect against these pathogens. This is a growing field and recent evidence supports that the composition and function of the microbiota can modulate the immune response of vaccination against respiratory viruses such as influenza and SARS-CoV-2. Recent studies have highlighted that molecules derived from the microbiome can have systemic effects, acting in distant organs. These molecules are recognized by the immune cells from the host and can trigger or modulate different responses, interfering with vaccination protection. Modulating the microbiota composition has been suggested as an approach to achieving more efficient protective immune responses. Studies in humans have reported associations between a better vaccine response and specific bacterial taxa. These associations vary among different vaccine strategies and are likely to be context-dependent. The use of prebiotics and probiotics in conjunction with vaccination demonstrated that bacterial components could act as adjuvants. Future microbiota-based interventions may potentially improve and optimize the responses of respiratory virus vaccines.